South Africa : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for South Africa. (IMF Staff Country Reports; Country Report ;, 2016)
South Africa has made considerable economic and social strides since 1994, but faces significant challenges. Deep-rooted structural problems-infrastructure bottlenecks, skill mismatches, and harmful insider-outsider dynamics-have kept unemployment and inequality unacceptably high. Also, a confluence of external and domestic shocks, combined with heightened governance concerns and policy uncertainty, have weighed on confidence and growth. Though private balance sheets are still strong, vulnerabilities are elevated. 2016 growth is projected at 0.1 percent. Only a muted recovery is envisaged from 2017, with rising unemployment. Downside risks dominate and stem mainly from China, heightened global financial volatility, and domestic politics and possible policy missteps. Shocks could be amplified by extensive macro-financial linkages, especially if combined with sovereign credit rating downgrades to speculative grade. On the upside, the recent dialogue between social partners could catalyze reform implementation and invigorate growth.